The W+ Standard: Incentivizing finance for women’s empowerment - Dominguez Fuentes, Larissa Eugenia (Women Organizing for Change in Agriculture and Natural Resource Management, 2023)
The session will introduce the W+ Standard and give an overview of the methodology for measuring women’s empowerment. The session will outline the set of steps to apply the W+ Standard—development of the project idea note, development of the project design document, gender analysis, data collection, interpretation of the data and development of the monitoring report. The second part of the session will focus on how the W+ Standard has evolved and our current scaling efforts—also providing insights on the results from the joint work with the Bill & Melinda Gates Foundation. This second part of the session will be more focused on sharing the challenges and opportunities we have found along the way, including collaborating with other Standard teams. Our oral presentation will introduce the Standard and methodology, with practical group exercises for each of the four steps of the methodology.